The intersection of globalization and renewable energy: India’s path to sustainable development by 2030 - Kashif Hasan Khan; Iman Bastanifar; Abdulmelik Alkan (Social Sciences and Humanities Open)
Globalization events have significantly shaped how major economies like India approach global challenges, especially in the energy sector. As the most populous country in 2024, India plays a crucial role in advancing renewable energy, aligned with the UN Sustainable Development Goal 7 for 2030. In 1990, India had a higher percentage of renewable energy consumption compared to 2020, even as the country saw improvements in its Globalization Index during this period. This raises the question: does increasing renewable energy consumption in India lead to a decline in globalization? To address this, we applied Least Squares estimation (Gauss-Newton/Marquardt steps) and GMM methods using EViews software to analyze the relationship between renewable energy consumption and the Globalization Index from 1990 to 2020. The results reveal an inverse U- shaped effect, where globalization increases when renewable energy consumption is below 34% but declines when it exceeds this threshold. Key global events, such as China’s Yuan inclusion in the SDR basket in 2016 and Iran’s energy policies, had minimal impact on India’s energy or globalization trends. However, the International North-South Transport Corridor (INSTC), revitalized after sanctions on Iran were lifted in 2015–2016, positively affected India’s global integration, making 2016 a pivotal year. Looking ahead to 2030, simulations suggest that strategic trade with INSTC members will boost India’s renewable energy use and Globalization Index, aligning with its commitment to cleaner energy and UN goals. India’s involvement in the Yuan internationalization, INSTC, and trade with Iran places it in a key position to contribute to the UN’s 2030 sustainability agenda.